Detached Statements - Mark McBride (Crítica)
Joseph Raz has introduced an interesting class of statements —detached statements— into the philosophical lexicon. In brief, such statements are (informa- tive) normative statements, yet the speaker does not, in so uttering them, express or convey acceptance of the point of view of the hearer to whom they are addressed (as contrasted with committed statements, where the speaker does express or convey such acceptance). I propose to offer a novel analysis of such statements (and to clear away some confusions about them). In brief, such statements will be analysed as wide-scope normative conditionals.